GAMBARAN PERBEDAAN KONSENTRASI EKSTRAK ETANOL DAUN KUNYIT (Curcuma longa L.) TERHADAP TOTAL FENOLIK SECARA SPEKTROFOTOMETRI VISIBEL - Aloysius Barry Anggoro; Yuliana Purwaningsih; FX Sulistiyanto WS; Erwin Indriyanti (Dian Nuswantoro Semarang, 2022)
Turmeric leaves (Curcuma longa L.) contain secondary metabolites, one of which is a phenolic compound. The choice of solvent is important in the extraction process, ethanol is chosen because it can attract compounds that are soluble in non-polar to polar solvents. The ethanol concentrations in this study were 60, 70, 80, and 96% with the extraction method used was maceration. The screening test obtained positive results for phenolic content. This is indicated by the appearance of a fluorescent blue-black stain on the plate after being sprayed with FeCl3 reagent. TLC test obtained comparison Rf value (gallic acid) is 0.53. Rf values for ethanol concentrations of 60, 70, 80, 90 and 96% were 0.53; 0.55; 0.57; 0.60; 0.60. The method used to determine the total phenolic content is folin-ciaocalteu. Analysis with visible spectrophotometry obtained the average total phenolic content of ethanol extract concentrations of 60, 70, 80, 90 and 96%, respectively 1.078; 1.796; 1.964; 1.842; and 1.787 GAE mg/g extract. The results of statistical tests obtained data that are normally distributed but not homogeneous, there are significant differences at concentrations of 60, 80, and 96%. The conclusion was that the highest phenolic content was in the ethanol extract of turmeric leaf with a concentration of 80%, there was an effect of ethanol concentration on the total phenolic content of the turmeric leaf ethanol extract, and there were differences in the total phenolic content at each concentration of ethanol used.Keywords :Turmeric Leaves (Curcuma longa L.), Total Phenolic Level, Ethanol Concentration, Visible Spectrophotometry